Analysis The Effect of Bidding Process on Project Performance in PT Pelabuhan Indonesia III (Persero) - Gita Prestalita; I Putu Artama Wiguna; Vita Ratnasari (IPTEK Journal of Proceedings Series, 2020)
Based on investment data in PT Pelabuhan Indonesia III (Persero) with asset code road and construction, also port facility construction in PT Pelabuhan Indonesia III (Persero) 2017 – 2018, there are 65 projects of physical construction. In the bidding process, to assess competence and business ability, also other requirements from the provider with stages of administration evaluation, technical evaluation and bid price from contractor. In 65 investment projects there are 18 projects fined. This research took 65 samples. While secondary data was collected from document of eligible awards of bidding on investment project in 2017–2018 in PT Pelabuhan Indonesia III (Persero) with asset code road and construction, also port facility. Analysis used was Structural Equation Modeling (SEM). The result of this research conclude that bidding process significantly affects to project performance variable